Natural hybridization between genetically differentiated populations of Crassostrea gigas and C-angulata highlighted by sequence variation in flanking regions of a microsatellite locus - Huvet, Arnaud; Fabioux, Caroline; Mccombie, Helen; Lapegue, Sylvie; Boudry, Pierre (Inter-Research, 2004)
The marine environment is of special interest for studying hybridization between closely related taxa because of the high dispersal potential of planktonic larvae, such as those of most bivalve species. The oysters Crassostrea angulata and C. gigas are known to be very close genetically and entirely inter-fertile under controlled conditions. However, hybridization in the wild had not been investigated, mainly due to the lack of nuclear diagnostic markers. In the present paper, we first estimated genetic differentiation between these 2 closely related taxa using 8 microsatellite markers. Interestingly, 5 markers displayed significant differences of allele size between taxa. The subsequent sequencing of alleles of one of these microsatellites showed several mutational events, which suggested null alleles and homoplasy. The presence of 1 insertion/deletion event in its 5' flanking sequence enabled us to design a new bi-allelic ('C' and 'NC') nuclear PCR-restriction fragment length polymorphism (-RFLP) marker (CG44R). This, together with a mitochondrial DNA marker, was used to analyze populations of C. angulata and C. gigas. The CG44R allele frequencies were very different between C. angulata (f[C] = 0.91) and C. gigas (f[NC] = 0.92) populations. This analysis also provided evidence for hybridization between C. angulata and C. gigas in a wild Portuguese population where the 2 taxa are in contact due to recent transportation of C. gigas stocks for aquacultural production. Our results represent the first indication of hybridization between these 2 taxa in the natural environment, and contribute to knowledge of the evolutionary history of the Crassostrea genus.